(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is devoted to the problem of continuity of traditions in the context of national culture, considered as a category, refracted through the prism of spiritual understanding. Spiritual heritage, which goes back to the past, includes the criteria of folk morality, practical recommendations of the organization of such a way of life, which is able to develop and contribute to the fact that each of its representatives by internal feelings, consciousness was focused in its activities on the preservation of sustainable rational foundations of national life. The problem of cultural heritage is becoming urgent today, especially issues such as what we should take from the world cultural heritage, how we should use the cultural values of historical and modern Kazakh society. Continuity is not only a priority of a certain sphere; it is a condition of existence of material and spiritual culture. The continuity of each national heritage reflects the history, the soul of the people, so it is an eternal source of spiritual and emotional experience for the new generation. Values acquired by past generations will never lose relevance, because each generation opens up new aspects of historical values relevant to the modern world. Preservation of historical traditions along with the adoption of civilizational values is an urgent task for the Kazakh culture in the XXI century. Key words: values, Kazakh culture, cultural heritage, continuity, civilization.